Legal Synchronization Limitations of Children Under Age in Positive Legal Perspectives in Indonesia - Mukhlis Mukhlis (Budapest International Research and Critics University, 2019)
The number of regulations regarding the age limit of a person said to be an adult in Indonesia actually creates legal uncertainty, because of the variety of these restrictions. Between the laws with one another it turns out to be mutually contradictory. Such a situation is certainly confusing for law enforcers such as judges to determine which laws will be chosen as the basis for deciding a case. One of the most interesting problems is the contradiction between Law No. 1 of 1974 concerning Marriage and Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection. According to Law No. 1 of 1974, 16 years of age for women are able to get married, while in Law No. 35 of 2004, the age of 16 is still said to be a child. The existence of these contradictions shows that legal inconsistency has resulted in legal uncertainty.